Improved performance of soy protein adhesive with melamine–urea–formaldehyde prepolymer. Issue 44 (9th August 2021) - Jiang, Ke; Lei, Zhenghui; Yi, Maoyu; Lv, Wenxin; Jing, Mingwei; Feng, Qiaoling; Tan, Hailu; Chen, Yuzhu; Xiao, Hui
Abstract : In recent years, soy protein adhesive, as an environmentally friendly bio-based adhesive, has attracted extensive attention. Abstract : In recent years, soy protein adhesive, as an environmentally friendly bio-based adhesive, has attracted extensive attention. In this study, in order to ameliorate the bonding quality of soy protein isolate (SPI) adhesive, the melamine–urea–formaldehyde prepolymer (MUFP) was synthesized, and different amounts of it were introduced into the SPI adhesive as a cross-linking agent. Fourier transform infrared (FT-IR) spectroscopy, gel permeation chromatography (GPC), thermogravimetric analyze (TGA), and scanning electron microscopy (SEM) were used to analysis the mechanism of modification. The results of plywood test indicated that the wet bonding strength of the adhesives was first increased and then decreased with an increase in the amount of MUFP additive. FT-IR, TGA, and SEM tests suggested that the introduction of MUFP could promote the establishment of a cross-linking structure in the cured adhesive layer to improve the bonding quality of adhesives, but presence of excessive MUFP could introduce hydrophilic groups and adversely affect water resistance.